Divergent role of nitric oxide in insulin‐stimulated aortic vasorelaxation between low‐ and high‐intrinsic aerobic capacity rats. Issue 7 (21st July 2015) - Crissey, Jacqueline M.; Padilla, Jaume; Vieira‐Potter, Victoria J.; Thorne, Pamela K.; Koch, Lauren G.; Britton, Steven L.; Thyfault, John P.; Laughlin, M. Harold
Abstract Low‐intrinsic aerobic capacity is associated with increased risk for cardiovascular and metabolic diseases and is a strong predictor of early mortality. The effects of intrinsic aerobic capacity on the vascular response to insulin are largely unknown. We tested the hypothesis that rats selectively bred for a low capacity to run (LCR) exhibit vascular dysfunction and impaired vascular reactivity to insulin compared to high capacity running (HCR) rats. Mature female LCR (n = 21) and HCR (n = 17) rats were maintained under sedentary conditions, and in vitro thoracic aortic vascular function was assessed. LCR exhibited greater body mass (13%), body fat (35%), and subcutaneous, perigonadal, and retroperitoneal adipose tissue mass, than HCR. During an intraperitoneal glucose tolerance test, glucose area under the curve (AUC) was not different but insulin AUC was 2‐fold greater in LCR than HCR. Acetylcholine and insulin‐stimulated aortic vasorelaxation was significantly greater in LCR (65.2 ± 3.8%, and 32.7 ± 4.1%) than HCR (55.0 ± 3.3%, and 16.7 ± 2.8%). Inhibition of nitric oxide synthase (NOS) with L‐NAME entirely abolished insulin‐mediated vasorelaxation in the aorta of LCR, with no effect in HCR. LCR rats exhibited greater expression of Insulin Receptor protein, lower Endothelin Receptor‐A protein, a down‐regulation of transcripts for markers of immune cell infiltration (CD11C, CD4, and F4/80) and up‐regulation of pro‐atherogenic inflammatory genes (VCAM‐1 and MCP‐1) in the aorta wall. Contrary to our hypothesis, low‐aerobic capacity was associated with enhanced aortic endothelial function and NO‐mediated reactivity to insulin, despite increased adiposity and evidence of whole body insulin resistance.